Derecho de contratos y excepcionalidad: reaparición de instituciones y retorno a los principios en contexto de Covid-19 - Edison Calahorrano Latorre (Universidad Hemisferios, 2020)
This paper analyzes the effects of the Covid-19 pandemic on Contract Law, specifically objective non-compliance and contractual remedies in the context of exceptionality. This study is dogmatic using analytical and comparative methods. The starting point is to verify whether the Covid-19 pandemic constitutes an act of God, by analyzing whether this phenomenon and its consequences meet the requirements of externality, unpredictability and irresistibility. From this response, contractual remedies are explored, such as rebus sic stantibus or the frustration of purpose of contract, its relationship with the principle of Contract Law pacta sunt servanda, and how they have been evoked in the legislation issued in exceptionality, for which a comparative analysis of the regulation of the leasing contract is developed. The nature of the principles as sources of law and their application in private law is then analyzed. Finally, it is concluded that contract law in exceptionality resorts to principles, understood as the rationalization of the rules, which allows for flexibility in the search for solutions to complexity.